ANALISIS HAMBATAN PROSES PEMBELAJARAN BIOLOGI DALAM PELAKSANAAN KURIKULUM 2013 BAGI GURU KELAS VII SMP DI KECAMATAN RAMBAH HILIR - Sayuti, Darmin (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
ABSTRACTThis research aims to determine biology barriers in the implementation Learning Process Curriculum 2013 for Junior High School teacher in the district Rambah Hilir. This research was carried out from July to December 2015. The method used descriptive qualitative by using a questionnaire. Population and sample of this research are 6 teachers from 11 schools. Results of this research is obtained from the analysis of questionnaire data with an average percentage of 87.97% with very good criteria. The barriers faced by teachers in the class VII SMP Rambah Hilir Rokan Hulu in biology learning process on the implementation of Curriculum 2013 is the availability of books and infrastructure are inadequate, training was too brief, which limited the use of media and the assessment is so difficult and requires a lot of time.